Tendencje w orzekaniu o potrzebie nauczania indywidualnego w województwie małopolskim - GAŁUSZKA, IZABELLA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Izabella Gałuszka, Tendencje w orzekaniu o potrzebie nauczania indywidualnego w województwie małopolskim [Tendencies in predication of the need for individual teaching in the Malopolska province]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 355-374. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.20 The article is devoted to individual teaching as a form of education for pupils whose health condition prevents or significantly impedes school attendance. It is awarded by public psychological and pedagogical counselors at every educational stage from pre-school to post-gymnasium. Due to the time of research and collected data, the theoretical part of the book can be found not only in the laws and regulations of 2017, but also in the regulations which are no longer binding. The purpose of the dissertation is to answer the questions: What is individual teaching? On what basis can this form of education be obtained? What are the possible consequences of individual teaching? In the research part, the author analyzes data obtained from the resources of deliberately selected psychological and pedagogical clinics in Małopolskie Voivodship. The analysis was compiled with data from the Statistical Office in Krakow concerning the school year 2014/2015 and discussed.